USE OF SODIUM-GLUCOSE TRANSPORT PROTEIN 2 (SGLT2) INHIBITORS IN DIABETIC KIDNEY DISEASE (DKD) - Manuel Rajagukguk, Rio (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
SGLT2 inhibitors have emerged as a major disease-modifying therapy for preventing the development of chronic kidney disease (CKD). These agents can be used to prevent the decline in renal function through the reduction of glomerular hypertension mediated through tubuloglomerular feedback apart from their effects on glycemic control. The indications for SGLT2 inhibitors have evolved based on growing evidence from randomized controlled trials and broadly fit into five categories, including: glycemic control/metabolic risk, reduced ASCVD, heart failure, diabetic kidney disease with albuminuria, and nondiabetic CKD with albuminuria. . The initial trial was performed in patients with relatively good overall renal function, although sub-analyses suggest that the beneficial effect may extend to patients with CKD. SGLT2 inhibitors block glucose reabsorption in the renal tubules and are effective in reducing glucose levels based on the amount of glucose filtered, thereby increasing the glomerular filtration rate. The greatest transport burden on the diabetic kidney is in the early proximal tubule. SGLT2 inhibitors make the transport load more evenly distributed between the tubular segments. In addition, the total tubular transport load is reduced by lowering GFR. The SGLT2 inhibitory effect helps maintain mitochondrial function and tubular cell metabolism which can maintain tubular function and GFR in the long term.